The Role of Empathy in Intergroup Conflicts - Budagova, Sabina (Scholarya Demo Journal of Ruby, 2020)
Throughout the history of mankind, the problem of intergroup conflict has been an integral part of relationships in society. In the hope of a peaceful conflict resolutions, scientists from different fields of science are actively studying this issue. Phenomen of empathy has received increasing empirical attention in the intergroup relations studies. A lot of those researches had been focused on the potential of interventions that generate empathy for reducing intergroup bias and improving intergroup attitudes. The relevance of this problem is based on demand to eliminate many social and political conflicts, both at the level of small and large groups. This article analyses the possibility of resolving intergroup conflicts through the use of the empathy mechanism. We define the term based on a historically consistent context. Further, the essence of two diagonally opposite emotions is revealed: distress and empathy. These statements are confirmed by a number of experiments cited in the article. Moreover, the mechanism of intergroup empathy is considered as one of the first and most important steps in the peaceful resolution of intergroup conflicts, and the conditions preceding the onset of empathy are analysed. Batson identified 4 basic conditions called empathy in studies of intergroup conflicts, as well as the effectsthey exhibit. A model that leads to an improvement in attitudes towards the opposite side of the conflict is also described. Empathy, in its true understanding, gives hope for a peaceful settlement of many conflicts, both at the level oflarge groups and at the level of small groups.